Political participation and social exclusion: latin american’s paradox convergence (2011)
T.H. Marshall’s classic text: “Citizenship and Social Class”, in which he discusses the interconnectedness of civil, political, and social rights, sti-pulates a positive relationship between democracy and social inclusion. The former provides a basis on which the losers of —socially polarizing— market processes can claim and obtain social rights.In fact, the experience of Western Europe exhibits an evolutionary pat-tern with regard to the expansion of the right to vote, followed by the expansion of the welfare state, which led to a marked decrease in income and wealth disparities in society. Marshall’s insight that the exercising of civil and political rights must be supplemented by additional social rights has become an unquestioned normative tenet in the industrialized countries. This seems to confirm the notion of a causallink between de-mocratic participation rights and the granting of social rights.